Polyostotic Fibrous Dysplasia with Epiphyseal Involvement in Long Bones: A Case Report - Tomoaki Fukui; Teruya Kawamoto; Toshiaki Hitora; Yoshiki Yamagami; Toshihiro Akisue; Tetsuji Yamamoto (Case Reports in Orthopedics)
Fibrous dysplasia (FD) is an uncommon, but well-known benign skeletal disorder. In cases affecting long bones, FD is commonly recognized to locate in the diaphyses or the metaphyses and to spare the epiphyses. In this paper, we present a rare case of polyostotic FD in a 13-year-old girl with unilateral multiple epiphyseal lesions arising in the femur, the tibia, and the fibula with the growth plates.